1997
DOI: 10.1039/a606270i
|View full text |Cite
|
Sign up to set email alerts
|

A novel host molecule p-[1-(4-hydroxyphenyl)-1-methylethyl]calix[8]arene. Synthesis and complexation properties in non-aqueous polar solution

Abstract: A novel deep-cavity calixarene, p-[1-(4-hydroxyphenyl)-1-methylethyl]calix[8]arene 1 was synthesized and its complexation with aromatic compounds was examined. Reaction of p-[1-(4-methoxyphenyl)-1-methylethyl]phenol 2 with paraformaldehyde under various conditions only resulted in p-[1-(4-methoxyphenyl)-1-methylethyl]calix[8]arene 3, and no corresponding calix[4]arene and calix[6]arene were detected. Removal of the methyl in the ether groups of 3 afforded 1 in 80% yield. Solubilization, fluorescence and photoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Despite the extended use of this family of compounds as hosts for inclusion complex formation, calixarenes have received much less attention from photochemists when compared with other host molecules of practical importance, even in solution studies. Very few photochemical studies of organic compounds within calixarenes were presented. …”
Section: Introductionmentioning
confidence: 99%
“…Despite the extended use of this family of compounds as hosts for inclusion complex formation, calixarenes have received much less attention from photochemists when compared with other host molecules of practical importance, even in solution studies. Very few photochemical studies of organic compounds within calixarenes were presented. …”
Section: Introductionmentioning
confidence: 99%
“…In this case, this calixarene compound capable to clamp the organic molecules. Calixarene compounds can be synthesized and derivatized at the "Lower Rim", therefore the part of upper rim calixarene rim is slow to develop [7]. Some type of adsorbent has been used to eliminate or reduce heavy metals, i.e.…”
Section: Introduction:-mentioning
confidence: 99%
“…Among those we quote the relevant report of the photophysical properties of the calix[8]arene-C 60 inclusion complex in the solid state [44], the diffuse reflectance laser flash-photolysis study of BZP and xanthone within calix[6]arene solid matrices [45] and also aqueous and non-aqueous [38,46,47] solution studies of several polycyclic aromatic compounds included within different calix[8]arenes. In the latter cases, inclusion complex formation was detected by pronounced fluorescence enhancement of the guests upon inclusion.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of calixarenes to form inclusion complexes, accommodating guest molecules or ions in their intramolecular cavities, greatly depends on the size and geometry of both guest molecule and host cavity [36][37][38]. In fact, experiments carried out with some polycyclic aromatic hydrocarbons possessing different dimensions and p-(diallylaminomethyl)calixarenes and p-(carboxyethyl)calixarenes showed that calix [4]arenes are too small to accept naphthalene and calix[8]arenes apparently are too small to accept coronene and decacyclene but sufficient to accommodate durene, naphtalene, anthracene, phenanthrene, fluoranthene, pyrene and perylene [37].…”
Section: Introductionmentioning
confidence: 99%